Application of the Therapy Group in Early Age as a Nursing Action in Prevention and Management of Napza Abuse - Saptiah Hasnawati; Herni Susanti; Ria Utami Panjaitan (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Drug abuse is a serious problem in every country. Indonesia is geographically located across two continents that allows illegal drugs to enter. More and more drug users, every year has increased. There is some research on drug cases including research on the prevention and handling of drug abuse. One way to handle this is to use group therapy. A review of the article to review the application of group therapy as an effort to prevent and manage drug abuse in young adults. Methods: reviewing articles through electronic database media; Pubmed, Proquest, EBSCO and Google Scholar. Keywords used group therapy, early adulthood, drug abuse. Selected articles in the range of 2010-2019 as many as 15 relevant articles are then narrowed down to 3 articles that meet the criteria. The concept obtained related to group therapy as an effort to prevent and manage drug abuse in young adults. There are types of group therapy namely Self Help Group (SHG), Cognitive Behavior Group Therapy (CBGT), Supportive Therapy (TS). Group therapy is possible as one of the non-pharmacological group therapies that can cause motivation, a feeling of security, get support and enthusiasm to recover and prevent the recurrence of drug use.